2020
DOI: 10.5860/crl.81.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Undesirable Difficulties: Investigating Barriers to Students’ Learning with Ebooks in a Semester-length Course

Abstract: Our ability to make informed decisions about ebooks is constrained by our limited understanding of how students perceive and use them. A team of librarians and a professor in learning sciences asked graduate students to serve as informants on student experience with ebooks. We analyzed student work in two semester-long studies, focusing on barriers and affordances they identified. In the first cohort, students who chose to explore ebooks uncovered affordances. In the second cohort, student comfort levels with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
5
0
3
Order By: Relevance
“…Le partage des stratégies d'apprentissage par l'enseignant ou encore de celles que déploient les étudiants peut s'avérer riche et bénéfique pour tous. Ce partage vient du même coup limiter les frustrations qui peuvent découler de l'utilisation des technologies numériques (Pierard et al, 2019). Enfin, les conditions relationnelles nous apparaissent essentielles pour assurer une présence à distance, comme le définit Jézégou (2010), en permettant des interactions, dès le premier contact, entre les étudiants et avec l'enseignant.…”
Section: Anticiper Et éValuer Les Pratiques Pédagogiques Pour Limiterunclassified
See 1 more Smart Citation
“…Le partage des stratégies d'apprentissage par l'enseignant ou encore de celles que déploient les étudiants peut s'avérer riche et bénéfique pour tous. Ce partage vient du même coup limiter les frustrations qui peuvent découler de l'utilisation des technologies numériques (Pierard et al, 2019). Enfin, les conditions relationnelles nous apparaissent essentielles pour assurer une présence à distance, comme le définit Jézégou (2010), en permettant des interactions, dès le premier contact, entre les étudiants et avec l'enseignant.…”
Section: Anticiper Et éValuer Les Pratiques Pédagogiques Pour Limiterunclassified
“…Plus encore, en établissant des attentes claires en ce qui concerne le déroulement du cours selon les modalités retenues, l'enseignant favorise la perception de l'étudiant envers les compétences à atteindre (Chekour et al, 2015). Également, cela permet à l'enseignant de comprendre comment les étudiants désirent utiliser les technologies mises à leur disposition (Pierard et al, 2019). Ces conditions ont toute leur importance dans le contexte de la pandémie, alors que les étudiants sont susceptibles de vivre davantage de stress, notamment par le fait qu'en étant hors campus, ils n'ont plus les mêmes repères en ce qui concerne leur vie universitaire, les services accessibles, etc.…”
Section: Anticiper Et éValuer Les Pratiques Pédagogiques Pour Limiterunclassified
“…A number of studies have related perceived barriers to a specific group. For example, Pierard et al (2020) dealt with e-books in school teaching. Their results confirmed various barriers that make it difficult for students to orient themselves, copy, and create notes directly in the text.…”
Section: Number Of E-books Per Yearmentioning
confidence: 99%
“…Cindy Pierard, Vanessa Lynn Svihla, Susanne K. Clement, and Bing-Shan Fazio discuss some concerns surrounding using library-licensed e-books to support course-assigned readings. 24 Students in their two-semester study noted more barriers than affordances to learning with e-books in courses; most frequently cited difficulties included navigation, printing and downloading difficulties, and interface design. Students in Mara Rojeski's study of e-books integrated into the LMS reported similar challenges.…”
Section: Introductionmentioning
confidence: 99%